(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Achieving a fully renewable energy future necessitates the integration of marine renewable energy sources, such as wave and tidal energy, into the current energy mix. These underutilized resources offer significant potential to enhance the reliability of renewable energy systems by complementing other climate-dependent sources, such as wind and solar energy, across various temporal scales. The inclusion of wave and tidal energy in the energy portfolio improves power output stability, reduces periods of energy generation shortfall, and lessens the dependency on energy storage solutions. This study employs innovative complementarity metrics—including total variation, variance, and standard deviation—to evaluate the interactions among wave, tidal, wind, and solar resources. A comparative analysis between the Mediterranean Sea conditions surrounding the Italian peninsula and the Atlantic Ocean conditions of Ireland reveals significant differences in the potential of wave and tidal energy. The complementarity analysis further underscores the advantages of diversifying the renewable energy mix, demonstrating that the inclusion of wave and tidal resources yields higher complementarity metrics and enhances the overall performance of the energy system in both regions.